Association of a COVID-19 diagnosis with adverse events, cohort design, follow-up starting on the day after time 0. - Shelby S. Fisher (22676406) (2025)
Association of a COVID-19 diagnosis with adverse events, cohort design, follow-up starting on the day after time 0.